THORIUM-URANIUM SYSTEMATICS REQUIRE LAYERED MANTLE CONVECTION - Turcotte D.L.; Paul D.; White W.M. (My University, 2001)
Two of the most important sources of information on the style of mantle convection come from geochemical constraints and mantle tomography. Constraints imposed by uranium-thorium systematics are examined in this paper. Observations require that the mid-ocean ridge basalt (MORB) source region be nearly homogeneous with a thorium-uranium ratio κ = 2.5±0.1. Simple mass balance considerations utilizing limits on the value of κ for the continental crust (κ<6) and a bulk earth value κ = 4.0±0.2 with heat production constraints show that the whole mantle has a thorium-uranium ratio greater than κ = 3.35±0.1. This leads to the conclusion that a substantial fraction of the mantle has a much more primitive value of κ (closer to 4.0) than the MORB source region. Our model assumes a near-uniform, depleted upper mantle that is the source region for MORB and has κ ≈ 2.5 and a near-primitive lower mantle with κ ≈ 4.0. Our results indicate that it is very difficult to have the upper mantle reservoir larger than 65% of the whole mantle and our preferred value is 45%. Three alternative hypotheses can be proposed: (1) A vertical stratification of κ through the mantle (since the role of whole mantle convection is to extract heat, the resulting vertical transport in the mantle would be expected to eliminate the vertical stratification of κ), (2) a mantle permeated with blobs (since the blobs would have to constitute some 65±10% of the mantle and be absent from the MORB source region, it is difficult to support this hypothesis), and (3) layered mantle convection with a compositional barrier to convection in the lower mantle. The results given here strongly favor this layered mantle hypothesis as recently set forth by Kellogg et al. [1999] and van der Hilst and Karason [1999].